Pilot study of a digital literacy-based intervention to confront concomitant crises amongst key food system actors in Chile - Kanter, Rebecca; Boza, Sofía; Acuña-Salazar, Paula (Frontiers in Sustainable Food Systems, 2023)
The fragility of food systems in Chile has been exposed through concomitant crises, from a social crisis in 2019, the COVID-19 pandemic, and climate change. The increased dependence on information and communication technologies (ICTs) to produce, sell and consume food and the digital divide have increased. The lack of digital literacy in Chile has not been evaluated or considered within comprehensive interventions. To examine how local food systems can be strengthened, we conducted a pilot study of a digital literacy-based intervention with smallholder farmers, vendors, consumers (n = 96) of different ages (25-45 y, and 46-65 y) from adjacent urban and rural regions in Chile. Telephone surveys were carried out on the use of ICTs, access to the food environment and agricultural practices during crises. A five-week digital literacy intervention was carried out on: digital confidence, use of ICTs to generate networks, networks, use of apps to sell or buy food, banking operations, and communication with state agencies. We also planned a virtual conversation about the food system and nutrition in Chile. All knew how to read and send WhatsApp messages, but >50% of farmers and vendors reported cell signal problems. Between the 2019 social crisis and COVID-19, supermarkets as the main source of food decreased from 79% to 57%, and delivery increased from 2% to 17%. 92% of the participants received the intervention, and 52% expressed satisfaction. Across participants, the average implementation score was 61%. Only one person connected to the virtual conversation. Crises have impacted how the Chilean population in both urban and rural regions navigate their food environment for their household as well as small-scale agricultural production in these areas; elucidating a greater dependency on ICTs amongst small-scale farmers, vendors, and consumers in Chile to buy and/or sell food. We also conclude that it is feasible to implement a digital literacy intervention for key food system actors in urban and rural settings in Chile. Future studies will contribute to the evidence base about the feasibility and impact of similar digital literacy interventions; an area of increasing importance given the rising prevalence of the digital food environment worldwide.